Diagnostic utility of specific electrocardiographical parameters in predicting left ventricular function - (:unkn) unknown (PULSUS GROUP INC, 2012)
A Cincin, B Ozben, O Erdogan. Diagnostic utility of specific electrocardiographical parameters in predicting left ventricular function. Exp Clin Cardiol 2012;17(4):210-214. BACKGROUND: Changes in electrocardiography (ECG) parameters, including sinus tachycardia, atrial fibrillation, bundle branch blocks, Q waves and left ventricular (LV) hypertrophy, are commonly observed in patients with heart failure (HF). OBJECTIVES: To determine whether specific ECG parameters have a diagnostic role in predicting LV systolic dysfunction (LVSD) in patients with suspected HF. METHODS: A total of 123 patients with symptoms or signs of HF and 20 HF patients with New York Heart Association class IV status were consecutively recruited. Several ECG parameters, including QRS duration, dispersion and SV1 or SV2 + RV5 or RV6 >= 3.5 mV (Goldberger's first criterion), QRS amplitude <= 0.8 mV in the limb leads (Goldberger's second criterion) and RV4/SV4 <1 (Goldberger's third criterion), were subsequently determined and correlated with LV ejection fraction (LVEF). RESULTS: One hundred six patients had LVEF <50% (LVSD group), while 37 patients had LVEF >= 50% (non-LVSD group). The maximal QRS duration of the LVSD group was significantly longer than that of the non-LVSD group (124.5+/-20.8 ms versus 109.7+/-13.1 ms; P<0.001). ROC analysis revealed that a cut-off point of QRS duration >= 124 ms significantly predicted LVSD (OR 4.1 [95% CI 1.7 to 10.2]; P=0.001). The frequencies of Goldberger's first and third criteria were higher in the LVSD group (OR 8.3 [95% CI 1.9 to 36.4]; P=0.001; and OR 8.9 [95% CI 3.4 to 23.2]; P<0.001, respectively). Logistic regression analysis showed that Goldberger's first and third criteria as well as QRS duration >= 124 ms were independent predictors of LVSD. CONCLUSION: Bedside ECG parameters, such as the Goldberger criteria, may be useful in predicting LVSD before the use of more sophisticated diagnostic tests is considered in patients with suspected HF.
Keywords: Echocardiography; ECG; Ejection fraction; Heart failure; QRS; QRS SCORING SYSTEM; CONGESTIVE-HEART-FAILURE; BRAIN NATRIURETIC PEPTIDE; MYOCARDIAL INFARCT SIZE; SYSTOLIC DYSFUNCTION; VOLTAGE RATIO; PRIMARY-CARE; ECG; POPULATION; LIMITATIONS